Phytoplankton and Equilibrium Concept: The Ecology of Steady-State Assemblages 2003
DOI: 10.1007/978-94-017-2666-5_5
|View full text |Cite
|
Sign up to set email alerts
|

Steady state phytoplankton in a deep pre-alpine lake: species and pigments of epilimnetic versus metalimnetic assemblages

Abstract: The vertical distribution pattern of algal species, chlorophylls and specific carotenoids present in the dimictic prealpine Ammersee (Bavaria, Germany) are given for the year 2001. A detailed taxonomic list of the phytoplankton species is recorded, along with light micrographs and detailed descriptions of the flagellates. A deep chorophyll maximum, mainly built by Planktothrix rubescens, was common in this deep mesotrophic lake. The three most dominant species among 83 identified taxa alternated seasonally and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
(36 reference statements)
2
7
0
Order By: Relevance
“…This finding agrees with other reports of phytoplankton composition in deep layers in lakes (Lindholm 1992, Gervais 1998, Knapp et al. 2003, Teubner et al. 2003).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding agrees with other reports of phytoplankton composition in deep layers in lakes (Lindholm 1992, Gervais 1998, Knapp et al. 2003, Teubner et al. 2003).…”
Section: Discussionsupporting
confidence: 93%
“…Violaxanthin occurs in some freshwater chrysophytes, but it reached only low concentrations due to low cell abundances in Mondsee. Investigation of individual marker pigments also made it possible to quantify specific taxonomic groups—for example, the close relationship between P. rubescens and oscillaxanthin in Mondsee, similar to findings reported from the deep chl maximum in prealpine Ammersee (Bavaria, Germany; Teubner et al. 2003).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Teubner et al, 2003;Reynolds, 2006), led to a moderate variability in both biomass and seasonal distribution of flagellates MFGs. Teubner et al, 2003;Reynolds, 2006), led to a moderate variability in both biomass and seasonal distribution of flagellates MFGs.…”
Section: Discussionmentioning
confidence: 99%
“…Jacquet et al, 2005. Teubner et al (2003) and Dokulil & Teubner (2005) reported that P. rubescens could develop considerable biomass at TP around 10 lg P L À1 , so it is surprising that P. rubescens did not develop at similar concentrations in Lake Bourget. Such episodic occurrences of P. rubescens were also observed in Lake Nantua and Mondsee (Feuillade, 1994;Dokulil & Teubner, 2012).…”
Section: Changes In Phosphorus and Phytoplankton Community Structurementioning
confidence: 99%